PENDIDIKAN ISLAM DI SEKOLAH MENENGAH ATAS SEBAGAI UPAYA MENANGKAL RADIKALISME - Barkatillah Barkatillah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Islamic education in high school should be able to counteract radicalism through the application of the values of Tawasuth, tawazun, I'tidal and Tasamuh. Therefore, the application of the values above is through IO (Instructional Objectives), EB (Entering/Entry Behavior), IP (Instructional Procedures) and PA (Performance Assessment).